End-To-End Web Testing with Cypress Explore Techniques for Automated Frontend Web Testing with Cypress and JavaScript. - Mwaura, Waweru (Packt Publishing, Limited, 2021)
Cypress is a JavaScript testing framework that does not require additional dependency to perform end-to-end testing, unlike Selenium. This book will help you to leverage the features of Cypress that make it one of the best testing platforms in the current testing landscape, and take you through writing and optimizing your own tests.